Job Safety Analysis Beam Fabrication And Ironing Activities At Santika Hotel Development Project – Sukabumi City - Dewi Chrisna Mayadani; Amarin Yudhana (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2024)
Accidents at work are a problem in Indonesia, especially in West Java. One of the jobs that has a high risk is the activity of fabricating and ironing beams. This work is structural work which is located on a critical path. The aim is to identify each stage of work up to OSH risk control in beam fabrication and ironing activities in the Santika – Nagrak Hotel Development project in Sukabumi Regency. The method in this study is qualitative by using interview techniques. The interview technique uses three informants, namely key informants, key informants and supporting informants. The data analysis used is the Miles and Hiberman method. The results of the data show that iron fabrication and beam ironing have a high risk of accidents and accidents have occurred, namely the risk of being pinched, falling from a height and being scratched. Meanwhile, the control measures undertaken by management are the provision of PPE, sockets equipped with lids or housings, carrying out routine checklists, conducting inductions for new workers, morning briefings and always reminding them of the applicable SOPs. OCCUPATIONAL HEALTH risk control in beam fabrication and procurement activities has been carried out by management so that workers remain safe at work.